Whey Forward: Reducing Total Solids for Cleaner Effluents and Value-Added Products using Reverse Centrifugal Expulsion - Deep, Ankit; Prasad, Kamlesh; Jindal, Navdeep (Indian Journal of Dairy Science, 2026)
Paneer production in India is still dominated by manual pressing, which is labour-intensive, inconsistent, and prone to nutrient loss in whey. To address this challenge, a semi-automatic reverse centrifugal expulsion prototype was utilised, integrating a processing vessel, insulated jacket, agitator, acid dosing unit, centrifugal pressing chamber, and control panel. The system was evaluated using a response surface design with coagulation temperature (70-80 °C), rotation speed (235.3-289.6 RPM), and pressing time (3-5 min) as key variables. Results showed that coagulation temperature was the most significant factor (p < 0.01) affecting whey composition and paneer yield, while pressing time had negligible influence. Regression models demonstrated high reliability (R² > 0.88), and experimental validation confirmed good agreement with predicted values (p < 0.05). Optimal conditions were identified as 70 °C coagulation temperature, 235.3 RPM, and 3 min pressing, yielding paneer with minimal whey nutrient loss. The study confirms that reverse centrifugal expulsion is a cost-effective, energy-efficient, and scalable technology for paneer manufacturing, offering small- and medium-scale dairies a sustainable alternative to conventional pressing while simultaneously reducing whey disposal challenges.